2015
DOI: 10.1016/j.medici.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function by speckle-tracking echocardiography in patients with low-T3 syndrome and acute myocardial infarction

Abstract: The late diastolic longitudinal LV strain rate and LV rotation evaluated by speckle-tracking echocardiography were impaired in patients with low-T3 syndrome after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Conventional echocardiography and speckle tracking techniques have become the preferred examination method in clinical treatment as they are non-invasive, reproducible, and high in sensitivity and accuracy (3). However, the measurements of this method are not stable (4). …”
Section: Introductionmentioning
confidence: 99%
“…Conventional echocardiography and speckle tracking techniques have become the preferred examination method in clinical treatment as they are non-invasive, reproducible, and high in sensitivity and accuracy (3). However, the measurements of this method are not stable (4). …”
Section: Introductionmentioning
confidence: 99%
“…In this subgroup analysis, a lower FT3/FT4 ratio was a stronger predictor of all-cause and cardiovascular mortality in patients with previous myocardial infarction ( 12 ). Another study involving 130 patients with AMI found that patients with low T3 syndrome had impaired late diastolic longitudinal strain rates and left ventricular rotation than those with normal T3, but T4 levels did not differ significantly between the 2 groups ( 33 ). Therefore, we hypothesized that patients with lower FT3/FT4 ratio in this sample might also have impaired cardiac function.…”
Section: Discussionmentioning
confidence: 99%